Excavation of resources of Streptomyces species in frozen soils of the Qinghai-Tibet Plateau based on RpfA protein of Streptomyces coelicolor - Xie, Yuxiao; Liu, Jingjing; Ma, Jun; Shi, Nan; Zhang, Xiumin (Frontiers in Microbiology, 2025)
This study is aimed at the actual demand for exploring new species resources of Streptomyces, and aims to solve the technical bottleneck of Streptomyces isolation and culture. A new method was established based on the resuscitation function of the RpfA protein from Streptomyces coelicolor CGMCC 4.1658T to isolate unculturable or difficult-to-culture Streptomyces species, and it was applied to explore Streptomyces species resources in special habitats in the frozen soils of the Qinghai-Tibet Plateau. The RpfA protein of S. coelicolor was heterologously expressed and validated for its in vitro activity. The purified RpfA protein was then used to isolate Streptomyces from soil samples in the frozen soils of the Qinghai-Tibet Plateau, followed by an investigation into the impact of the RpfA protein on the cultivability of Streptomyces species. The results showed that the RpfA protein had a significant promoting effect on the germination of spores of both S. coelicolor itself and other species of the Streptomyces genus, and when a suitable concentration of RpfA protein was added to the culture medium, it could significantly improve the culturability of members of phylum Actinomycetota, especially Streptomyces species. In addition, many new species of the genus Streptomyces and other genera of phylum Actinomycetota were discovered. This study provides a new approach for further exploring Streptomyces species resources in special environments such as the Qinghai-Tibet Plateau and developing new biologically active substances produced by Streptomyces.